Cost-effectiveness of nivolumab plus ipilimumab as first-line treatment for American patients with unresectable malignant pleural mesothelioma - Zhuo-miao Ye; Zi-Qing Tang; Zhe Xu; Qin Zhou; Huan Li (Frontiers Media S.A., 2022)
BackgroundThe treatment paradigm of unresectable malignant pleural mesothelioma (MPM) has changed in recent years. Checkmate 743 demonstrate that nivolumab plus ipilimumab showed good clinical benefits compared with chemotherapy in the treatment of MPM. The study is aim to evaluate the cost-effectiveness of Nivolumab plus ipilimumab vs. platinum plus chemotherapy for the first-line treatment of unresectable MPM.MethodsA Markov model was developed to compare the cost and quality-adjusted life-year (QALY) of nivolumab plus ipilimumab and chemotherapy over a 10-year time horizon. Clinical efficacy and safety data were extracted from the CheckMate 743 trials. Health state utilities were obtained from published literature. Costs were collected from an US payer perspective. One-way and probabilistic sensitivity analyses were conducted to explore the impact of uncertainties on the cost-effectiveness's results.ResultsIn the base case analysis, the incremental healthcare costs and QALYs for Nivolumab plus Ipilimumab vs. chemotherapy are $196,604.22 and 0.53, respectively, resulting an incremental cost-effectiveness ratio (ICER) of $372,414.28/QALYs for the model cohort of patients with locally advanced or metastatic MPM. However, Probabilistic sensitivity analysis showed that there was no probability that Nivolumab plus ipilimumab was cost-effective within the fluctuation range of other model parameters in first-line in unresectable MPM. The results of one-way sensitivity analysis showed that the cost of Nivolumab was the most sensitive parameter.ConclusionsThe ICER of Nivolumab plus ipilimumab is above the theoretical willingness-to-pay threshold in the U.S, which suggests that first-line nivolumab plus ipilimumab for unresectable MPM may be not a cost-effective choice.